2022
DOI: 10.1177/02557614211073138
|View full text |Cite
|
Sign up to set email alerts
|

Why (not) be a music teacher? Exploring pre-service music teachers’ sources of concern regarding their future profession

Abstract: There is a global shortage of music teachers, and this deficit is continually growing. While there is a considerable body of research on the sources of concern, attrition, stress and burnout for practising teachers, studies investigating the perspective of pre-service music teachers instead are comparatively rarer. This gap in the literature is problematic, considering its relevance to the development of teacher education programmes and the prevention of discouragement and unrealistic expectations among teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This paucity notwithstanding, we found some interesting insights into this topic from Nordic studies in other areas, such as community music and pre-service teachers’ concerns. For example, the participants of a sample similar to ours did not express any concern about their choice of main instrument, with one exception: singing in relation to classical music, which was seen as an “instrument” that is “almost non-existent in today’s society” (Mateos-Moreno, 2022). In addition, instruments seen as more suited for accompanying dance (e.g., violin and guitar) may be prioritised within community music contexts in Sweden (Söderman & Westvall, 2017).…”
Section: Frameworkmentioning
confidence: 86%
“…This paucity notwithstanding, we found some interesting insights into this topic from Nordic studies in other areas, such as community music and pre-service teachers’ concerns. For example, the participants of a sample similar to ours did not express any concern about their choice of main instrument, with one exception: singing in relation to classical music, which was seen as an “instrument” that is “almost non-existent in today’s society” (Mateos-Moreno, 2022). In addition, instruments seen as more suited for accompanying dance (e.g., violin and guitar) may be prioritised within community music contexts in Sweden (Söderman & Westvall, 2017).…”
Section: Frameworkmentioning
confidence: 86%
“…The dilemmatic condition of teachers' appreciation is not an uncommon discourse. For example, a recent study conducted by previous study state teacher candidates revolved around employment conditions and appreciation, such as low income compared to other professions (Mateos-Moreno, 2022) in the Swedish pre-service teacher education context revealed that the biggest concern expressed by Sw. Even in a developed country like Sweden, the extrinsic aspects (e.g., working contexts) were still reported as the major concerns for teacher candidates.…”
Section: Discussionmentioning
confidence: 99%
“…By looking ahead to the future projections of themselves as a future teacher, they can be nurtured in becoming the desired teachers they wish to become in the future (Beauchamp & Thomas, 2010;Dinham et al, 2017). The inevitable concerns possessed by teacher candidates should be identified and discussed thoroughly by teacher educators in order to maintain their wellbeing and prevent teacher attrition and burnout (Blackley et al, 2018;Mateos-Moreno, 2022). It is essential to explore whether the 'new normal' practices of teaching influence the way teacher candidates project their future practices and selves.…”
Section: Discussionmentioning
confidence: 99%
“…Case studies allow an in-depth exploration of the complexity and uniqueness of a particular topic from multiple perspectives in a real-life context (Simons, 2014). The chosen case is particularly compelling for exploring this topic due to its prestige within the Nordic countries and the substantial emphasis on teaching practices integrated into its music education program since the first year; thereby enabling students to develop particularly well-informed beliefs about the profession (Mateos-Moreno, 2022b).…”
Section: Methodsmentioning
confidence: 99%